Effect of silver nanoparticles on different Candida species isolated from patients with oral candidiasis. - Marwa Bahey; Basant Gabr; Amr Gabr; Alaa Abo Hagar; Eman Hegazy (Microbes and Infectious Diseases)
Background: Oral candidiasis is an opportunistic infection of the oral cavity that can be distributed via the bloodstream, resulting in serious systemic candidiasis. Because of the toxicity and side effects of antifungal agents, research on the antifungal impact of silver nanoparticles (AgNPs) is necessary. Methods: Oral swabs were collected from fifty patients with oral candidiasis for the isolation and identification of candida species by automated Vitek 2. Biofilm formation was evaluated using a tissue culture plate assay. The anti-candida and anti-biofilm effects of AgNPs on isolated Candida species were investigated using agar-well diffusion and microdilution methods. Results: Candida albicans was the predominant isolate, accounting for 51.9%. Biofilm formation was identified in 63.5% of candida isolates, commonly in isolates of C. albicans (57.6%), C. tropicalis (30.3%), and C. parapsilosis (12.1%), while all C. glabarata isolates could not form a biofilm. A significant decrease in the growth of candida isolates was detected at 500 μg/mL of AgNPs. The largest zone of inhibition (22.6 mm ± 0.6) was detected with C. albicans, then C. parapsilosis (20.4 mm ± 0.9), C. tropicalis (18.4 mm ± 0.5), and C. glabrata (16.5 mm ± 0.6) with a statistically significant difference. AgNPs inhibited the biofilm production of Candida species up to 100% at 500 μg/ml. Generally, the AgNPs anti-biofilm activity was significantly higher against C. albicans than C. tropicalis and C. parapsilosis at concentrations ranging from 31.25 to 250 μg/ml. Conclusions: Synthesized AgNPs showed antifungal and antibiofilm activity against all albicans and non-albicans Candida species.